A review on the short-term strategy for reducing the peak-valley difference and the long-term energy structure optimization strategy in cities based on the integration of “power generation - power grid - power load - Energy storage” - Shi, Yiting; Zhang, Liting; Yang, Yongwen; Li, Qifen; Zhang, Hanzhou (Frontiers in Energy Research, 2025)
Effectively alleviating the contradiction in load regulation brought about by the peak-valley difference of electricity is an important measure to promote the high-quality development of energy and electricity in the new era and realize the optimization of the energy structure. As a city entering a new stage of development as an ultra-large-scale urban economy, Shanghai has a strong external dependence on energy and a shortage of available resources within the city. Coupled with factors such as the connection of a high proportion of renewable energy sources, the uncertainty on the power supply side has increased, resulting in a shortage of short-term electricity power and obstruction to the optimization of the long-term energy structure. Therefore, in view of the characteristics and formation causes of the peak-valley difference in Shanghai, combined with the energy structure within the city and the situation of power supply connections from outside the city, the fundamental reasons for the continuous widening of the peak-valley difference in Shanghai’s electricity and the bottleneck encountered in the adjustment of the energy structure are deeply explored. On this basis, the research status and development trends of technical measures on each side of “Source-Grid-Load-Storage” are sorted out, and a technical system applicable to reducing the peak-valley difference and realizing the optimization of the energy structure in Shanghai is refined and established. Further multi-time dimension and multi-index contribution degree evaluations are carried out to strengthen forward-looking strategic guidance and top-level layout planning.